Inspection and maintenance of reinforced and prestressed concrete structures (FIP guide to good practice., 1986)
The extent of the investment in concrete structures has emphasized the need to maintain these structures. This guide describes various types of damage, which may be discovered, and the equipment used to carry out inspections. It includes suggested inspection intervals, related to the severity of loadings and environmental conditions.